Readiness of medical students for self-directed learning under competency based medical education - A cross-sectional study - G Anusha; Chitra Nagaraj; D Shobhitha; R Anil (Wolters Kluwer Medknow Publications, 2024)
Introduction: National Medical Commission (NMC) has introduced Competency-Based Medical Education (CBME) for undergraduates (UG) of medical stream in India. Self-directed Learning (SDL) has become a vital part of CBME curriculum, such that NMC mentions some SDL hours can go beyond office hours if required. Therefore, assessing SDL becomes important among the UG medical students (MBBS). Objectives: To assess the readiness towards SDL method among the medical students under CBME curriculum and to find out the factors associated with their readiness towards SDL method. Subjects and Methods: It was a cross-sectional study conducted among the MBBS students under CBME curriculum studying at PESIMSR, Kuppam. All the 300 students were included with 241 participating in the study. Abridged Fisher's 29 item SDL readiness scale was used. Data were compiled and analyzed using the SPSS (version 23.0; SPSS Inc., Chicago, IL, USA). Results: Among 241 students, the SDL readiness was found be below average, average and above average in 2%, 66% and 32% respectively. The above average category of SDL readiness was higher (36.07%) among the 1st CBME batch of students than compared to the 2nd batch (27.7%). SDL was found to be statistically significantly associated (P < 0.05) with age, mode of admission, parents' involvement in the learning process, stress in life and self-confidence of the students. Conclusion: The readiness to undergo SDL varies from student to student. Therefore, understanding their readiness is necessary to sensitize them regarding SDL method. By this, the students can achieve the SDL-based competencies in a better way.